Sub Mucous Cleft Palate and Its Diagnosis and Management - Pradhan, Bhawani (Medical Journal of Shree Birendra Hospital, 2010)
Four different age groups of cases came to hospital with the complaint of severely nasalized speech and since childhood. Parents had already consulted to the physician in one of the valley Hospital who referred the patient for speech therapy without a clinical diagnosed as sub mucous cleft (SMC). Speech pathologist has to confirm of sub mucous cleft palate with the help of the plastic surgeon. Sub mucous cleft palate is a significant cause of severs speech and language disorder. Aim of the paper is to make the clinician and laymen aware of the sub mucous cleft palate which is less commonly diagnosed partly due to ignorance and misdiagnosis. Sub mucous cleft is the cleft of muscle and bony portion of palate it has got triad characters:- Bifid uvular, thin bluish line in the margin raphe (septum palludine) & hyper nasality. And we could feel palpable sign and speech and language disorder. It may have also lots of related problems like mental retarted, hearing loss, behavior problems etc. Sub mucous cleft, is diagnosed and management by team approach like plastic surgeon, E.N.T. Surgeon, Dental surgeon, sp & lag pathologist and audiologist etc. Speech therapy is the one of the essential area for their better quality of life after surgery. DOI: 10.3126/mjsbh.v9i1.3488 Medical Journal of Shree Birendra Hospital Vol.9(1) 2010 28-31